The Twelve dogs of Christmas [compact disc, unabridged] - Rosenfelt, David (Rosenfelt, David. Andy Carpenter novels., 2016)
Christmas novel featuring reluctant criminal defense lawyer Andy Carpenter and his faithful golden retriever, Tara, that delivers Rosenfelt's trademark humor, larger-than-life characters, and twisting plotlines.